METODOLOGI TERJEMAHAN AL-QUR’AN DALAM AL-QUR’AN DAN TERJEMAHNYA BAHASA BATAK ANGKOLA - Nst, Hanapi (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2019)
This paper is a study of the methodology of the translation of the Qur'an translation of Al-Quran dan terrjemahnya bahasa Batak Angkola. The problem to be answered is whether the translating team translates from Al-Qur'an (Arabic) or translates from the Indonesian language published by the Ministry of Religion. In addition, This research also answers how the methodology of translating the Qur'an and the translation of the Angkola Batak Language. The method used in this study is by exploring, reviewing the literatures and also interviewing the translation of the book. As a result, the methodology applied in the Qur'an and the translation of the Angkola Batak Language is the methodology of word-for-word translation, literal translation, semantic translation, and communicative translation. Keywords: Al-Qur'an and the translation of Angkola Batak Language, Methodology